Peran Ketua Rumah Tahfidz Baitul Mu’min Dalam Mengelola Pendidikan Karakter Anak - Dai, Rekal; Herson Anwar; Syahrial Labaso (CV. ITTC INDONESIA, 2026)
This study aims to examine the role of the Head of Rumah Tahfidz Baitul Mu’min in Tibawa District, Gorontalo Regency, in managing children’s character education, as well as to identify the obstacles and challenges encountered in its implementation. This research employed a qualitative approach and was conducted at Rumah Tahfidz Baitul Mu’min, Isimu Selatan Village. The data sources consisted of primary and secondary data collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results indicate that the management of children’s character education at TPQ Rumah Tahfidz Baitul Mu’min is implemented in an integrated manner, with the Head of TPQ playing a strategic role in planning, directing, and supervising educational activities, including coordinating with teachers and providing exemplary behavior. The character education methods applied include role modeling, habituation, advice, supervision, and evaluation. The obstacles faced consist of internal factors such as limited teaching staff, facilities, and diverse backgrounds of students, as well as external factors such as lack of family support and the influence of gadget use. The main challenge lies in maintaining consistency and sustainability in the implementation of character education programs.